1967
DOI: 10.1515/znb-1967-1122
|View full text |Cite
|
Sign up to set email alerts
|

II. Lokalisation von Enzymen des reduktiven und dem oxydativen Pentosephosphat-Zyklus in den Chloroplasten und Permeabilität der Chloroplasten-Membran gegenüber Metaboliten

Abstract: 1. The interrelationship of metabolic activities in chloroplasts and cytoplasm of leaf cells of spinach, sugar beet and Elodea has been investigated. Different methods have been adopted to study the intracellular localization of enzymes and the flow of phosphorylated intermediates across the chloroplast membrane. The flow of substrates was investigated by determining the rates of the conversion of substrates added to aqueously isolated chloroplasts, prior to and after destruction of the outer chloroplast membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0
1

Year Published

1975
1975
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 0 publications
3
26
0
1
Order By: Relevance
“…1.1.1.43) are present in spinach chloroplasts [13], three assays were performed to show that the presence of 6-phosphogluconate dehydrogenase does not interfere with assaying glucose-6-phosphate dehydrogenase. One assay contained 1.0 mM glucose-6-phosphate and 1.0 mM 6-phosphogluconate, the other two contained all ingredients plus glucose-6-phosphate or 6-phosphogluconate, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…1.1.1.43) are present in spinach chloroplasts [13], three assays were performed to show that the presence of 6-phosphogluconate dehydrogenase does not interfere with assaying glucose-6-phosphate dehydrogenase. One assay contained 1.0 mM glucose-6-phosphate and 1.0 mM 6-phosphogluconate, the other two contained all ingredients plus glucose-6-phosphate or 6-phosphogluconate, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Through cell fractionation, G6PDH and 6PGDH activities were detected in both chloroplasts and cytosol (Garnier-Dardart, 1965;Heber et al, 1967;Slack and Hatch, 1967;Latzko and Gibbs, 1968;Mukerji and Ting, 1968;Miflin and Beevers, 1974 , 1973;Simcox and Dennis, 1978;Nishimura and Beevers, 1981), it was widely assumed thereafter, yet never clearly demonstrated, that a11 other activities of the pathway also occur as such isoenzymes and are compartmentalized in the same manner.…”
mentioning
confidence: 99%
“…Although many cell fractionation studies (Heber et al, 1967;Emes and Fowler, 1978;Feierabend and Gringel, 1983) indicated that most of the activities in the OPPP core segment may be confined to plastids, one notable report assumed that about 70% of these activities were cytosolic (Latzko and Gibbs, 1968) in spinach leaves. Attempts to distinguish plastid-and cytosol-specific isoenzymes of Rib-5-P isomerase and transketolase from various tissues (Rutner, 1970;Kawashima and Tanabe, 1976;Feierabend and Gringel, 1983) were mostly unsuccessful, and it was recognized (Feierabend and Gringel, 1983) that the cyclic mode of the cytosolic OPPP would be problematic in the absence of corresponding isoenzymes.…”
mentioning
confidence: 99%
“…When enzyme activities are present in both cell compartments, they are due to isoenzymes, one located in the chloroplasts and the other in the cytosol (1, 2, 4). This distribution also applies to the two key enzymes of the oxidative pentose phosphate cycle, glucose-6-P dehydrogenase and 6-P-gluconate dehydrogenase (11,25,26).…”
Section: Introductionmentioning
confidence: 96%
“…When enzyme activities are present in both cell compartments, they are due to isoenzymes, one located in the chloroplasts and the other in the cytosol (1, 2, 4). This distribution also applies to the two key enzymes of the oxidative pentose phosphate cycle, glucose-6-P dehydrogenase and 6-P-gluconate dehydrogenase (11,25,26).At present only little evidence is available about the intra-'This investigation was supported by the Deutsche Forschungsgemeinschaft. cellular distribution of enzymes in etiolated plant tissues, since most work has been performed using green leaves.…”
mentioning
confidence: 98%